Summary of the best evidence for the use of antiseptics at various surgical sites to prevent postoperative infections - Du, Qingqing; Wu, Shan; Jin, Ziwei; Ni, Li (Frontiers in Medicine, 2025)
ObjectiveTo retrieve and summarize the best available evidence regarding the use of antiseptics at various surgical sites to prevent postoperative infections.MethodsFollowing the “6S” evidence model, a comprehensive search was conducted across guideline repositories, professional association websites, and both Chinese and English databases. The search covered literature from database inception through December 2024. Two researchers trained in evidence-based nursing independently screened the literature, assessed quality, extracted data, and synthesized the findings.ResultsA total of 30 studies met the inclusion criteria, consisting of 3 clinical decision support documents, 5 guidelines, 4 expert consensuses, 9 systematic reviews, and 9 evidence summaries. In total, 36 pieces of evidence were integrated across five key areas: general principles, recommended antiseptics for specific surgical sites, application methods, handling of special circumstances, and quality control.ConclusionThis study compiles the best current evidence on antiseptic use across different surgical sites for preventing postoperative infections. It lays a foundation for standardizing disinfection protocols and improving infection control in clinical practice. Healthcare professionals are encouraged to integrate this evidence with individual patient conditions and clinical judgment.